Effects of supplementation with krill oil on blood parameters, hair quality, and fecal microbiota in male beagle dogs - Wang, Wencan; Xu, Ling; Cao, Yong; Liu, Guo; Zhang, Yan; Wang, Xi; Mao, Xin (Frontiers in Microbiology, 2025)
Krill oil (KO) is a bioactive substance with antioxidant and immunomodulatory functions. This study investigated the impact of administering snacks supplemented with 0.5% KO for 8 weeks on the blood parameters, hair quality, and fecal microbiota in dogs. KO was determined to elevate the activities of serum superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and immunoglobulin G (IgG) level. Concurrently, KO markedly diminished serum tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-8 (IL-8), and malondialdehyde (MDA) levels in dogs. The KO group displayed a considerably higher ratio of ideal scores and thinner hair scales for newborn hair, as well as a significant increase in total amino acid and methionine (Met) content in comparison to the control group. Furthermore, 16S rRNA sequencing revealed the changes in the composition of fecal microbiota after KO feeding. KO significantly affected the α and β diversity of canine fecal microbiota. Moreover, KO augmented the relative abundance of Bacteroidota, Actinobacteriota, and Proteobacteria at the phylum level, and it increased the relative abundance of Allobaculum, Bifidobacterium, Prevotella_9, Collinsella, and Turicibacter at the genus level. In summary, this study provides valuable insights to further understand the role of KO in promoting canine health.